2008
DOI: 10.1016/j.jmb.2008.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Folding of a LysM Domain: Entropy-Enthalpy Compensation in the Transition State of an Ideal Two-state Folder

Abstract: Protein-engineering methods (Φ-values) were used to investigate the folding transition state of a lysin motif (LysM) domain from Escherichia coli membrane-bound lytic murein transglycosylase D. This domain consists of just 48 structured residues in a symmetrical βααβ arrangement and is the smallest αβ protein yet investigated using these methods. An extensive mutational analysis revealed a highly robust folding pathway with no detectable transition state plasticity, indicating that LysM is an example of an ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 44 publications
6
31
0
Order By: Relevance
“…The fact that the value of Δ G °(0) determined from the FRET method is comparable to that (1.2 ± 0.2 kcal/mol) determined from CD spectroscopy (Figure 7) validates the FRET method. In addition, this result is also consistent with the study of Nickson et al (35), which showed that the Δ G ° for the unfolding of the LysM domain is 3.0 kcal/mol at 10 °C and pH 7. Since the LysM domain is more stable at neutral pH and lower temperatures (35), under the current experimental conditions (pH 5.8 and 20 °C) the LysM domain is expected to exhibit a smaller Δ G °(0).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The fact that the value of Δ G °(0) determined from the FRET method is comparable to that (1.2 ± 0.2 kcal/mol) determined from CD spectroscopy (Figure 7) validates the FRET method. In addition, this result is also consistent with the study of Nickson et al (35), which showed that the Δ G ° for the unfolding of the LysM domain is 3.0 kcal/mol at 10 °C and pH 7. Since the LysM domain is more stable at neutral pH and lower temperatures (35), under the current experimental conditions (pH 5.8 and 20 °C) the LysM domain is expected to exhibit a smaller Δ G °(0).…”
Section: Resultssupporting
confidence: 92%
“…In addition, it contains a single Trp residue (sequence, SITYRVRKG-DSLSSIAKRH-GVNIKDVMRW-NSDTANLQPG-DKLTLFVK), thus making it convenient to employ the proposed FRET study. More importantly, Nickson et al (35) have recently used extensive Φ-value analyses to show that LysM is an ideal two-state folder and the Δ G for unfolding at 10 °C is 3.0 kcal/mol. To conduct the proposed FRET study, we replaced the C-terminal Lys residue with Phe CN and the resultant mutant is called LysM-P hereafter.…”
mentioning
confidence: 99%
“…A foldon originally referred to a discrete, contiguous section of a polypeptide chain consistent with the principle of minimum frustration [59]. This term was later extended to include any nucleation-competent sub-motif in a protein [60]. Herein, a foldon refers to a highly cooperative group that shows independent thermodynamic and kinetic behaviors; thus, one may classify, according to its thermodynamic behavior, the residues belonging to the same cooperative group as a macro-unit, referred to as a foldon by Englander [5,[56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…This method has been successfully applied to characterize transition states for protein folding (1,2), for proteinprotein interactions (3)(4)(5) and for conformational changes in folded proteins (6). Protein folding transition states were shown to have native-like topology in the whole protein or in major parts of the structure (7)(8)(9) and it is commonly assumed that this includes the presence of native-like secondary structure (10,11). Because site-directed mutagenesis can only modify amino acid side chains, it is still unclear at which stage of a folding reaction backbone hydrogen bonds in secondary structure elements are formed.…”
mentioning
confidence: 99%